The Relationship Between Education Level and Public Knowledge of Malaria in East Seram Regency, Maluku - Kailola, Nathalie Elizcheva; Seimahuira, Theresia Natalia; Lekatompessy , Jerome Constantine (Journal of Public Health Sciences, 2025)
Malaria remains a significant public health challenge in tropical regions, including East Seram Regency in Maluku Province, which continues to experience high malaria endemicity. Community education plays a vital role in shaping health literacy and malaria knowledge. This cross-sectional study examined the association between education level and malaria knowledge among 253 randomly selected respondents using a validated questionnaire. Logistic regression analysis examined the relationship between education, healthcare facility visits, and malaria knowledge. The findings indicated that higher education level was strongly associated with better malaria knowledge (OR=6.93; 95% CI: 1.89–25.45; p=0.003). Respondents who had visited health facilities were more likely to have good malaria knowledge (OR=2.45; 95% CI: 1.38–2.90; p=0.001). Other variables, including gender, marital status, income, and age, were not statistically significant after adjustment. To reduce malaria burden, scalable interventions should prioritize educational outreach and improve access to quality health services. Integrating these strategies into regional malaria control programs can enhance community health literacy and support sustainable prevention efforts.